A learner-centered approach to teaching the physics of climate during the COVID-19 pandemic - Rehfeld, Kira (Heidelberg inspirations for innovative teaching, 2021)
Earth’s climate is changing, and the pace and direction of this change are driven by the increasing anthropogenic greenhouse gas emissions into the atmosphere and the action of Earth system feedbacks. The M.Sc. course ‘Physics of Climate’ at Heidelberg University aims to provide students with an advanced understanding of the climate system and the methods to study it. In the summer term 2020, I co-taught this course in a team with two other lecturers and two tutors. My contribution was structured to emphasize the learners’ actions and for the students to develop a connected, reflected, scientific workflow. This led to the introduction of climate models as a new topic and we enhanced the weekly exercises towards that goal. In class, we designed an overarching climate modeling experiment in which the rotation rate of the Earth (inversely related to the day length) was varied from 0.25 times the present rotation rate to 2 times. We first established that fundamental equations do not allow us to predict the changes in atmospheric circulation. Therefore, students formed hypotheses on climate impacts, performed the model experiments, and analyzed and discussed the results. Due to the COVID-19 pandemic, the course was taught exclusively online. This resulted in challenges regarding communication, equipment, and the additional workload for the teaching team as well as for the students. More than thirty-five participants successfully completed the course. Overall, the learner-centered approach increased the preparation time for the lecturer and tutors. This was due to the combination of the general situation early on in the pandemic and technical unknowns. The high degree of motivation observable from the students also required constant attention, while the technical setup of the climate model required some adjustments to the planned experiments further into the course. This paper documents the course design and execution and how we addressed the challenges following a constructivist approach to learning. The learning outcomes were not assessed in a way that would allow a quantitative comparison to traditional “homework-based” teaching. Nevertheless, the student papers and presentations highlight the high level of understanding of the dynamics, complexity, and structures in the climate system that students achieved.